A Review Paper on Smart Irrigation System (International Journal of Innovative Research in Computer Science & Technology, 2020)
Human demands are rising day by day as a  result of the growing population. Simultaneously, the need  for food materials is growing. In order to satisfy food  demand, crop production efficiency must be improved in  situations when labour and water are scarce. The necessity  of the time is to make effective use of existing labour,  water, and fertilisers in order to reduce the cost of yearly  crop production. Luckily, technology today as well as  practices may help you achieve your cost-cutting and  quality-control goals. This preliminary research focuses on  a low-cost automated smart irrigation system that  conserves water and human labour while providing the  desired quantity and quality of crops. The suggested  system also includes a basic yet compact smart phone  application that allows the farmer to carry out watering and  fertilisation regimens. The experimental setup at the farm  measuring 1 acre of sugarcane production demonstrated a  56 percent decrease decrease in water consumption, a 90  % decrease in labor expenditures for irrigation, and a 75  percent reduction in power consumption when compared  to the conventional procedures. As a consequence, the  proposed strategy produces a win-win situation for both  farmers and the government, which is currently competing  for water and power in our country.
Keywords: GSM Module; Human; Soil; Sensor